2019
DOI: 10.21776/ub.jam.2019.017.03.11
|View full text |Cite
|
Sign up to set email alerts
|

Determining Factors of Student’s Entrepreneurial Intention in Indonesia: A Meta-Analysis

Abstract: This study aims to conduct a meta-analysison determining factors that affect student's entrepreneurial intention. There are a variety of findings from several studies on the influence of the variables on entrepreneurial intention (Zhao et al., 2010; Bae et al., 2014). According to Wolf (1986), there is a need for synthesis on the various findings of several studies by using a meta-analysis approach.The meta-analysis procedure adopts the procedure by Baeet al.(2014), which includes sample identification for met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
(5 reference statements)
1
3
0
Order By: Relevance
“…variable that has a very strong influence on entrepreneurial intention compared to other variables(Vamvaka et al, 2020) [7]. This is in line with research conducted byWahjudono et al (2019), which in his research showed that five factors strongly influenced the results of students' entrepreneurial intention, namely perceived feasibility/behavioral control, self-efficacy, personal attitudes towards entrepreneurial, need for achievement, and adversity quotient. Another study added that the existence of entrepreneurship education significantly strengthens the attitude of individuals in determining their entrepreneurial intention.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…variable that has a very strong influence on entrepreneurial intention compared to other variables(Vamvaka et al, 2020) [7]. This is in line with research conducted byWahjudono et al (2019), which in his research showed that five factors strongly influenced the results of students' entrepreneurial intention, namely perceived feasibility/behavioral control, self-efficacy, personal attitudes towards entrepreneurial, need for achievement, and adversity quotient. Another study added that the existence of entrepreneurship education significantly strengthens the attitude of individuals in determining their entrepreneurial intention.…”
supporting
confidence: 85%
“…Research conducted by Bae et al (Wahjudono et al, 2019) [1] shows positive and moderate results between entrepreneurial intention and entrepreneurship education. According to Rachwal (2010), entrepreneurship education is not only crucial in developing entrepreneurial attitudes, but in stimulating entrepreneurship in general (Wach & Wojciechowski, 2016) [2].…”
Section: Introductionmentioning
confidence: 92%
“…small and medium-sized businesses, succeed because entrepreneurs are creative and intelligent, can keep up with technological developments and actively use them. They also have more motivation and recognition (Aghniya & Subroto, 2021;Armani, 2022;Wahjudono et al, 2019;Waluyo et al, 2022)…”
Section: Online Business Successmentioning
confidence: 99%
“…Entrepreneurship was measured using seven items from (Mauer et al, 2009). Measuring online business effectiveness using 7 items adapted from (Wahjudono et al, 2019). The questionnaire asked participants to rate each statement from 1 (strongly disagree) to 5 (strongly agree).…”
Section: Instrument Development and Data Analysismentioning
confidence: 99%